Paroxetine effects in adult male rat colon: Focus on gut steroidogenesis and microbiota. (September 2022) - Diviccaro, Silvia; Giatti, Silvia; Cioffi, Lucia; Falvo, Eva; Piazza, Rocco; Caruso, Donatella; Melcangi, Roberto C.
Abstract: Paroxetine, a selective serotonin reuptake inhibitor (SSRI), is prescribed to treat psychiatric disorders, although an off-label SSRI use is also for functional gastrointestinal disorders. The mutual correlation between serotonin and peripheral sex steroids has been reported, however little attention to sex steroids synthesized by gut, has been given so far. Indeed, whether SSRIs, may also influence the gut steroid production, immediately after treatment and/or after suspension, is still unclear. The finding that gut possesses steroidogenic capability is of particular relevance, also for the existence of the gut-microbiota-brain axis, where gut microbiota represents a key orchestrator. On this basis, adult male rats were treated daily for two weeks with paroxetine or vehicle and, 24 h after treatment and at 1 month of withdrawal, steroid environment and gut microbiota were evaluated. Results obtained reveal that paroxetine significantly affects steroid levels, only in the colon but not in plasma. In particular, steroid modifications observed immediately after treatment are not overlap with those detected at withdrawal. Additionally, paroxetine treatment and its withdrawal impact gut microbiota populations differently. Altogether, these results suggest a biphasic effect of the drug treatment in the gut both on steroidogenesis and microbiota. Highlights: Gut steroidogenesis is influenced by paroxetine treatment. Gut microbiota is influenced by paroxetine treatment. An increase of pregnenolone levels occurs at paroxetine withdrawal. Paroxetine withdrawal affects gut microbiota.